Factors Associated with Husbands' Participation in the Family Planning Program - Eka Yustina; Rahmad Gurusinga; Raisha Octavariny; Karnirius Harefa; Reni Aprinawaty Sirait (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
Husband participation in family planning (FP) programs is a key factor in the success of population control and the improvement of family reproductive health. However, the level of husband involvement in FP programs in Indonesia remains relatively low and is influenced by various factors. This study aims to analyze the relationship between knowledge, attitudes, the role of health workers, and sociocultural factors with husband participation in family planning programs. This study employs a quantitative research design with a cross-sectional approach. The study population consists of married couples of reproductive age, with the sample selected using purposive sampling. Data collection was conducted using a structured questionnaire. Data analysis was performed using univariate and bivariate methods with the chi-square test, as well as multivariate analysis using multiple logistic regression to identify the dominant factors influencing husbands’ participation in family planning programs. The results indicate a significant relationship between knowledge, attitudes, and sociocultural factors and husbands’ participation in family planning programs (p < 0.05). Meanwhile, health workers did not show a significant association with husbands’ participation (p > 0.05). The knowledge variable was the factor most strongly associated with husbands’ participation in the family planning program, with a 1.65-fold higher likelihood of participating compared to husbands with lower knowledge levels, whereas attitudes and sociocultural factors did not show a significant influence after controlling for other variables. This study indicates that husbands’ participation in family planning programs is influenced by individual and environmental factors, particularly husbands’ knowledge regarding family planning. Therefore, efforts to enhance education and outreach focused on husbands, as well as sociocultural approaches involving families and communities, are needed to increase men’s involvement in family planning programs.